Transcendental philosophy and naturalism - Smith, Joel R. (Joel Robert), 1944-; Sullivan, Peter M., 1958- (Oxford : Oxford University Press, 2011)
Kant's introduction of a distinctive form of philosophical investigation and proof, known as transcendental, inaugurated a new philosophical tradition. In this volume eight original essays assess the present state and contemporary relevance of this tradition and its relation to the naturalistic tendency in recent philosophy.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Transcendentalism; Naturalism; Kant, Immanuel, -- 1724-1804.